Frank Wild - J. M. W. (Polar Record, 1940)
Frank Wild's death must have been the first thought of Antarctic men meeting each other this winter. Apart from the leaders, no other Antarctic figure has so impressed himself on so many of the rank and file as Wild; for he had been a member of no less than five great expeditions, second in command on the later ones, but on all, whether in high position or not, acting as the guide and instructor to those new to Antarctic work.